Circadian Period 2 (Per2) downregulate inhibitor of differentiation 3 (Id3) expression via PTEN/AKT/Smad5 axis to inhibits glioma cell proliferation. Issue 5 (2nd May 2022) - Zhang, Yifan; Hu, Xvlei; Li, Hailiang; Yao, Jian; Yang, Ping; Lan, Yuanxiang; Xia, Hechun
ABSTRACT: In this study, we employed multiple laboratory techniques to acknowledge the biological activities and processes of Per2 and Id3 in glioma. We analyzed TCGA and CGGA databases for seeking association among Per2, Id3, and clinical features in glioma. Immunohistochemistry and Western blot were used to detect protein expression levels. CCK-8 assay, colony formation assay, Transwell assay, the wound healing assay, flow cytometric, and Xenograft nude mice were used to acknowledge the impact of Per2 and Id3 on biological behavior of glioma. The results showed that the Per2 mRNA expression was negatively correlated with the WHO grade, while the Id3 mRNA expression was positively correlated with the WHO grade in patients with glioma in TCGA and CGGA databases. Per2 and Id3 maintained separate prognostic abilities and had a negative connection in human glioma. In the clinical sample study, Per2 and Id3 were validated at the protein level with the same results compared to the mRNA expression level in TCGA and CGGA. By using a wide range of functional examples, overexpression of Per2 restrains malignant biological behaviors in glioma cells by many ways, while Id3 promotes malignant biological behaviors in glioma cells. Furthermore, overexpression of Per2 can inhibit Id3 expression via regulating PTEN/AKT/Smad5 signaling pathway and thereby abolish malignant biological behaviors that are caused by Id3 overexpression. These results suggested that Per2 inhibits glioma cell proliferation through regulating PTEN/AKT/Smad5/Id3 signaling pathway, which may be a viable therapeutic target for glioma. Graphical abstract: uf0001